Chapter Progettare percorsi didattici di Storia della scuola per le scuole secondarie di II grado - Martinelli, Chiara (Public History of Education. Teorie, esperienze, strumenti, 2022)
The paper deals with how Public History and Public History of Education can be applied in secondary schools. Several advantages can be achieved through their presence: firstly, they enhance the role of workshops in studying history; secondly, they increase the motivation in Special Education Needs students. Three project works will be presented as they show how Public History of Education can stimulate interdisciplinarity.